Phenylpropanoid profiling reveals a class of hydroxycinnamoyl glucaric acid conjugates in Isatis tinctoria leaves. (December 2017) - Nguyen, Thi-Kieu-Oanh; Jamali, Arash; Grand, Eric; Morreel, Kris; Marcelo, Paulo; Gontier, Eric; Dauwe, Rebecca
Abstract: The brassicaceous herb, Isatis tinctoria, is an ancient medicinal plant whose rosette leaf extracts have anti-inflammatory and anti-allergic activity. Brassicaceae are known to accumulate a variety of phenylpropanoids in their rosette leaves acting as antioxidants and a UV-B shield, and these compounds often have pharmacological potential. Nevertheless, knowledge about the phenylpropanoid content of I. tinctoria leaves remains limited to the characterization of a number of flavonoids. In this research, we profiled the methanol extracts of I. tinctoria fresh leaf extracts by liquid chromatography – mass spectrometry (LC-MS) and focused on the phenylpropanoid derivatives. We report the structural characterization of 99 compounds including 18 flavonoids, 21 mono- or oligolignols, 2 benzenoids, and a wide spectrum of 58 hydroxycinnamic acid esters. Besides the sinapate esters of malate, glucose and gentiobiose, which are typical of brassicaceous plants, these conjugates comprised a large variety of glucaric acid esters that have not previously been reported in plants. Feeding with 13 C6 -glucaric acid showed that glucaric acid is an acyl acceptor of an as yet unknown acyltransferase activity in I. tinctoria rosette leaves. The large amount of hydroxycinnamic acid derivatives changes radically our view of the woad metabolite profile and potentially contributes to the pharmacological activity of I. tinctoria leaf extracts. Graphical abstract: Highlights: The phenylpropanoids in Isatis tinctoria rosette leaves are profiled by LC-MS. The profile contains flavonoids, hydroxycinnamic acid esters and oligolignols. We reveal a large class of hydroxycinnamoyl glucaric acid esters. Fed 13 C6 labeled glucaric acid serves as a substrate for hydroxycinnamoyl transfer.